2018
DOI: 10.5812/jhealthscope.68266
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quality of Work Life and Burnout: A Linear Regression Structural-Equation Modeling

Abstract: Background: Most health professions, including nursing, create a lot of stress. To alleviate and cope with stresses and strains of the job, awareness of the causes is essential. Burnout and quality of work life are among factors affecting employees' performance degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
(34 reference statements)
1
12
0
1
Order By: Relevance
“…In Farsi et al's study, quality of work life was significantly correlated with the two components of emotional exhaustion and personal accomplishment. However, in the present study, only emotional exhaustion correlated significantly with quality of work life (28) .In a study carried out by Ashrafi et al on nursing, it was revealed that quality of work life has a significant negative association with job burnout, which is consistent with results of the current study (29). Moreover, Karim's findings on prison staff indicated that there was a significant association between job burnout and quality of work life (30).…”
Section: Discussionsupporting
confidence: 89%
“…In Farsi et al's study, quality of work life was significantly correlated with the two components of emotional exhaustion and personal accomplishment. However, in the present study, only emotional exhaustion correlated significantly with quality of work life (28) .In a study carried out by Ashrafi et al on nursing, it was revealed that quality of work life has a significant negative association with job burnout, which is consistent with results of the current study (29). Moreover, Karim's findings on prison staff indicated that there was a significant association between job burnout and quality of work life (30).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the professional aspect, job burnout has been associated with absenteeism, decreased productivity, organizational commitment, motivation and satisfaction [ 3 , 5 , 10 ]; reduced physical and mental health and affecting the quality of work [ 72 ]. In fact, the level of satisfaction in the workplace is found to have a decisive influence on workers’ health [ 73 ].…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…In fact, the level of satisfaction in the workplace is found to have a decisive influence on workers’ health [ 73 ]. Lower levels of burnout are found in people with a greater interest in their jobs [ 72 ]. On the other hand, high levels of burnout were reported as possibly indicating a negative attitude towards work and oneself, lack of interest and lack of satisfaction with one’s work [ 74 ].…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The findings of some studies have also indicated that having a good level of QWL would reduce employee complaints and work-related absences (Uysal et al, 2018). In contrast, undesirable QWL can make employees prone to mental disorders (Biglari et al, 2014) and increase turnover rate and burnout symptoms (Ashrafi et al, 2018;Jafari et al, 2017). In addition, undesirable QWL could influence depersonalization (Permarupan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside these studies, there has been a high volumes researches conducted to identify mechanisms through which QWL can affect the mentioned outputs. Ashrafi et al (2018) demonstrated that the effect of QWL on outputs such as personal accomplishment, emotional exhaustion, and depersonalization might be mediated by burnout. Likewise, Salehi et al (2020) demonstrated that the effect QWL on psychological well-being is mediated by burnout.…”
Section: Introductionmentioning
confidence: 99%